LncRNA IGFL2-AS1 as a ceRNA Promotes HCT116 Cell Malignant Proliferation via the miR-433-3p/PAK4 Axis - Liu, Shuang; Wang, Xiangjie; Zhang, Jing; Liu, Yabin; Li, Binghui (Turkish Journal of Gastroenterology, 2023)
Background: Colorectal cancer is a common gastrointestinal malignancy worldwide. Many studies have proved that long noncoding RNA alterations participate in colorectal cancer development. This study sought to probe the regulatory mechanism of lncRNA IGF-like family member 2 antisense RNA 1 (IGFL2-AS1) in colorectal cancer cell malignant proliferation. Methods: LncRNA IGFL2-AS1 expression in colorectal cancer cancer and para-cancerous tissues and colorectal cancer cell lines was detected via quantitative real-time polymerase chain reaction. HCT116 cells were transfected with si-IGFL2-AS1, microRNA (miR)- 433-3p inhibitor or p21 (RAC1)-activated kinase 4, PAK4 and IGFL2-AS1 overexpression vector, followed by assessment of cell proliferation and clone formation using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay and colony formation assay. The subcellular localization of lncRNA IGFL2-AS1 was predicted and testified via the nuclear/cytosol fractionation assay. The downstream miRNA of lncRNA IGFL2-AS1 and downstream target of miRNA were predicted, and their binding relationships were testified using dualluciferase assay and RNA immunoprediction experiment. Results: LncRNA IGFL2-AS1 was abundantly expressed in colorectal cancer tissues and cells. Silencing lncRNA IGFL2-AS1 discouraged HCT116 cell malignant proliferation, while lncRNA IGFL2-AS1 overexpression played an opposite role. LncRNA IGFL2-AS1 was mainly expressed in the cytoplasm of HCT116 cells. LncRNA IGFL2-AS1 bound to miR-433-3p and inhibited its expression. miR-433-3p targeted PAK4. Silencing lncRNA IGFL2-AS1 facilitated miR-433-3p to suppress PAK4 transcription. miR-433-3p inhibition or PAK4 overexpression partly reversed the inhibition of lncRNA IGFL2-AS1 on HCT116 cell malignant proliferation. Conclusion: LncRNA IGFL2-AS1 was abundantly expressed in colorectal cancer tissues and cells, and comparatively bound to miR433-3p to facilitate PAK4 transcription, thus promoting HCT116 cell malignant proliferation. Cite this article as: Liu S, Wang X, Zhang J, Liu Y, Li B. LncRNA IGFL2-AS1 as a ceRNA promotes HCT116 cell malignant proliferation via the miR-433-3p/PAK4 axis. Turk J Gastroenterol. 2023;34(5):497-507.